Covalently immobilized chemically modified lysozyme as a sorbent for bacterial endotoxins (lipopolysaccharides) - Levashov, Pavel A. (Biotechnol Rep (Amst), 2019)
Chemical modification of lysozyme was carried out using benzaldehyde and anisaldehyde. It was shown that chemical modification affects only 1–2 amino groups of the protein molecule which does not prevent further covalent immobilization of lysozyme using the remaining free amino groups. The bacteriolytic activity of lysozyme is preserved after chemical modification and after subsequent covalent immobilization. As a result of chemical modification immobilized lysozyme more effectively adsorbs bacterial lipopolysaccharides (endotoxins). Adsorption of immunoglobulin G does not increase after modification. The sorbents obtained in this work can be used for the future development of new medical material for the extracorporeal treatment of sepsis. The proposed scheme for the modification and immobilization of lysozyme can be used with various aldehydes for the preparation of sorbents with different properties.